The Effect of Peak Area Estimation on the Gamma-Ray Spectrum Analysis - Fattah, Aziz H. (Sulaimani Journal for Pure and Applied Sciences, 2008)
This paper deals with a measured gamma-ray spectrum and designing a MATLAB program to perform peak finding procedure by using the differences of the experimental data as well as performing fitting process by using Newton-Gauss least square technique. Then, five different methods of peak area determination are proposed to analyze the symmetry lines of Po212 in the spectrum, and the comparison was done using the percentage variance reduction test.
Keywords: Nuclear physics; Gamma ray spectrum; Peak area determination